Correction: Levicar et al. Methods of Radiographic Measurements of Heart and Left Atrial Size in Dogs with and without Myxomatous Mitral Valve Disease: Intra- and Interobserver Agreement and Practicability of Different Methods. Animals 2022, 12, 2531 - Charanthorn Levicar; Ingo Nolte; José Luis Granados-Soler; Fritjof Freise; Jonathan Friedemann Raue; Jan-Peter Bach (Animals)
In the original publication by Levicar et al [...]